(untitled) (PANGEEA, 2025)
The evolution of hydrographical network in the Alba Iulia area. The large size of Oiejdea-Şard corridor and Ampoi corridor could not form through erosion of valleys with debit and power erosion as Cricău or Ampoi rivers. Corridors was formed by a river much higher, as the Mures. The study of Mures developments and other smaller rivers in the area led to a model of river network evolution that can explain the current size of the corridor and appearance of the hydrographical network.